The Significance of Neutrophil-Lymphocyte Ratio and Mean Corpuscular Volume in Diagnosis of Preeclampsia - Çağlar Yıldız; Savaş Karakuş; Özlem Bozoklu Akkar; Tuğba Topbaş; Meral Çetin; Ali Yanık; Ali Çetin (Medical Network, 2016)
OBJECTIVE: The aim of this study is to evaluate the diagnostic values of neutrophil to lymphocyte ratio (NLR) and mean corpuscular volume (MCV) in patients with preeclampsia. STUDY DESIGN: A retrospective analysis of patients with documented preeclampsia and uncomplicated pregnancy was carried out. Two hundred and twelve women with preeclampsia, and 58 healthy pregnant women as controls were included in the study. NLR and MCV values were calculated from complete blood count analysis. RESULTS: White blood cell, NLR and MCV values were higher in the preeclamptic patients than those of the controls. The study groups had similar features with regard to the maternal age, gravidity, parity, and mode of delivery. Gestational age, newborn weight, and Apgar scores of the newborns were found lower in the preeclampsia group. CONCLUSION: NLR may be helpful in the differential diagnosis of preeclampsia. Large-scale prospective studies with categorized study groups according to the severity of preeclampsia need to be performed to determine the optimal NLR values useful for the assessment of severity of preeclampsia.